Antimetastatic potentials of salvianolic acid A on oral squamous cell carcinoma by targeting MMP‐2 and the c‐Raf/MEK/ERK pathway. Issue 5 (31st January 2018) - Fang, Chih‐Yuan; Wu, Ching‐Zong; Chen, Pei‐Ni; Chang, Yu‐Chao; Chuang, Chun‐Yi; Lai, Chih‐Ting; Yang, Shun‐Fa; Tsai, Lo‐Lin
Abstract: The metastasis of oral squamous cell carcinoma (OSCC) is one of the most important causes of cancer‐related deaths. Thus, various therapeutic strategies have been developed to prevent the metastasis of OSCC. Salvianolic acid A (SAA), a traditional Chinese medicine, has antithrombosis, antiplatelet, anti‐inflammation, and antitumor activities. Here, we provide molecular evidence indicating that SAA exerts its antimetastatic effects by markedly inhibiting the invasion and migration of oral squamous SCC‐9 and SCC‐25 cells. SCC‐9 and SCC‐25 cells were treated with various concentrations of SAA to further investigate the precise involvement of SAA in cancer metastasis. The results of zymography, and Western blotting indicated that SAA treatment may decrease matrix metallopoteinase‐2 (MMP‐2) expression. SAA also inhibited p‐c‐Raf, p‐MEK1/2, and p‐ERK1/2 protein expression. In addition, treating SCC‐9 cells with U0126, a MEK‐specific inhibitor, decreased MMP‐2 expression and concomitantly inhibited cell migration. Our findings suggested that SAA inhibits the invasion and migration of OSCC by inhibiting the c‐Raf/MEK/ERK pathways that control MMP‐2 expression. Our findings provide new insights into the molecular mechanisms that underlie the antimetastatic effect of SAA and are thus valuable for the development of treatment strategies for metastatic OSCC.